Animal Models of Neurodevelopmental Disorders - Yager, Jerome Y. (Neuromethods, 2015)
Providing a spectrum of models that is reflective of the various species that can be utilized in experimentation on disorders across a broad range of developmental disabilities, this volume collects expert contributions involved in investigation of the causes, outcomes, treatment, and prevention. Animal Models of Neurodevelopmental Disorders explores models of perinatal hypoxia-ischemia/cerebral palsy and stroke, autism spectrum disorder, fetal alcohol syndrome, as well as mental retardation. Written in the popular Neuromethods series style, chapters include the kind of detail and key advice from the specialists needed to get successful results in your own laboratory. Practical and authoritative, Animal Models of Neurodevelopmental Disorders serves to introduce and entice those interested in better understanding and treating these disorders to the vital animal model world of investigation